2003
DOI: 10.1093/ps/82.12.1925
|View full text |Cite
|
Sign up to set email alerts
|

β-Mannanase ameliorates viscosity-associated depression of growth in broiler chickens fed guar germ and hull fractions

Abstract: High concentrations of guar meal in broiler chicken diets reduce body weight and feed efficiency. The increased intestinal viscosity that is responsible for reduced measures of performance results from residual guar gum present in guar meal. Two experiments were designed to study the effects of 2 guar meal fractions at 3 different concentrations, germ (0, 5.0, and 7.5%) and hull (0, 2.5, and 5.0%), and the effectiveness of a beta-mannanase at three levels (0, 1x, and 4x; 1x = 1.09 x 10(5) units/ kg) on broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 15 publications
8
84
0
2
Order By: Relevance
“…Some studies reported that there was no negative impact on productive performance after adding GM without enzyme to diets at concentrations up to 2.5% in broiler chicks (Lee et al, 2003a;2003b) or 5% in laying hen diets (Gutierrez et al, 2007). Different indigestible polysaccharides, such as pectin, gum Arabic, gum agar, locust bean gum and guar gum, increase intestinal viscosity, which decreases growth and increases feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that there was no negative impact on productive performance after adding GM without enzyme to diets at concentrations up to 2.5% in broiler chicks (Lee et al, 2003a;2003b) or 5% in laying hen diets (Gutierrez et al, 2007). Different indigestible polysaccharides, such as pectin, gum Arabic, gum agar, locust bean gum and guar gum, increase intestinal viscosity, which decreases growth and increases feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Heat treatment and supple- (Patel and McGinnis, 1985;Lee et al, 2003a;2003b;2009) (Table 3). Theenzymes like pectinase in chick feed have also been recommended for overcoming growth-inhibitory properties of GM (Anderson and Warnick, 1964;Rao et al, 2015).…”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…Flow diagram depicting overall guar meal processing steps of feed mills (Figure 3). Patel and McGinnis, 1985;Lee et al, 2003a;2003b;2009) …”
Section: Methods To Improve the Nutritive Value Of Guar Mealmentioning
confidence: 99%
“…To remove some of the beans odour and gum residual from Guar Meal (GM), it is toasted being subjected to steam and dry heat (Rahman and Leighton, 1968). Feeding characteristics and other properties of GM have been well evaluated in poultry nutrition (Couch et al, 1967;Verma and McNab, 1982;Lee et al, 2003a;2003b;Hassan et al, 2008). However, few experiments have been done to evaluate the chemical composition and nutritive value of different guar meals for ruminant nutrition.…”
Section: Introductionmentioning
confidence: 99%